2020
DOI: 10.34293/education.v9i1.3494
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Competencies for Inclusive Education: Will Emotional Intelligence do Justice?

Abstract: Purpose: The concept of inclusive education is moved from the homogeneous perspective to heterogeneous perspective in developed countries and even in developing countries, the discourses on inclusive education are argued from the diversity perspective. Many scholars (Florian, 2010; Slee, 2010; Meijer, 2003 and; Allan, 2011) who are researching on inclusive education debated and discussed that successful practice of inclusive education depends greatly on teacher competencies, albeit practicing inclusive educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
(26 reference statements)
2
4
0
1
Order By: Relevance
“…That is, students tend to perform better in university settings when they can functionally understand and regulate their emotions. The finding could confirm previous attempts about the association between the overall EQ score and AA ( Partido and Stafford, 2018 ; Denny et al, 2019 ; Suleman et al, 2019 ; MacCann et al, 2020 ; Pozo-Rico and Sandoval, 2020 ; Rajendran et al, 2020 ; Sánchez-Álvarez et al, 2020 ); however, regarding the sub-components, while other studies found positive associations between intrapersonal, adaptability, stress management, and general mood sub-components and English language students’ AA ( Parker et al, 2004 ; Fahim and Pishghadam, 2007 ), the findings of this study could only confirm the association between general mood and AA. It can imply that students are more academically successful only if they are in a good mood which might be generated in classroom settings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That is, students tend to perform better in university settings when they can functionally understand and regulate their emotions. The finding could confirm previous attempts about the association between the overall EQ score and AA ( Partido and Stafford, 2018 ; Denny et al, 2019 ; Suleman et al, 2019 ; MacCann et al, 2020 ; Pozo-Rico and Sandoval, 2020 ; Rajendran et al, 2020 ; Sánchez-Álvarez et al, 2020 ); however, regarding the sub-components, while other studies found positive associations between intrapersonal, adaptability, stress management, and general mood sub-components and English language students’ AA ( Parker et al, 2004 ; Fahim and Pishghadam, 2007 ), the findings of this study could only confirm the association between general mood and AA. It can imply that students are more academically successful only if they are in a good mood which might be generated in classroom settings.…”
Section: Discussionsupporting
confidence: 89%
“…To compensate for the lack of consistency in the relationship between IQ and AA, and following the recognition that IQ is not the sole predictor of academic success, researchers started to examine the association between EQ and AA. The majority of research in this regard has also found it a core competency that is positively correlated with and can predict individuals’ AA ( Partido and Stafford, 2018 ; Denny et al, 2019 ; Suleman et al, 2019 ; MacCann et al, 2020 ; Pozo-Rico and Sandoval, 2020 ; Rajendran et al, 2020 ; Sánchez-Álvarez et al, 2020 ). Higher levels of EQ can improve students’ self-confidence and their ability to overcome challenges leading them toward better academic performance ( Jan and Anwar, 2019 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Providing guidance and advice makes children have ideals; providing supervision over their learning is to provide motivation and rewards so that children are encouraged to learn and excel, while the fulfillment of the facilities needed in learning is so that children are more firmly established in an idealism to be achieved by utilizing available facilities there is. The forms of parental participation in the development of children's achievements include: Giving encouragement to children about the importance of education for their children's future, as a facilitator for all children's activities, being a source of knowledge and knowledge in the family, motivating children to continuously improve learning achievement they, as a place to ask questions and complain about things that are children's problems, provide clear directions for their children's future (Kurt & Taş, 2018;Rajendran et al, 2020).…”
Section: Counseling For Studentsmentioning
confidence: 99%
“…Teacher competence and teacher attitudes are critical because, in the end, the teacher is responsible for educating students with various characteristics in the classroom and can apply educational principles (Rajendran et al, 2020). Several factors influence the development of teacher competence.…”
Section: Introductionmentioning
confidence: 99%